Treatment decision for recurrences in non-small cell lung cancer during or after adjuvant osimertinib: an international Delphi consensus report - Mirza, Myriam; Shrivastava, Aseem; Matthews, Cecile; Leighl, Natasha; Ng, Calvin S. H.; Planchard, David; Popat, Sanjay; Rotow, Julia; Smit, Egbert F.; Soo, Ross; Tsuboi, Masahiro; Yang, Fan; et al. (Frontiers in Oncology, 2024)
Introduction Osimertinib is recommended by major guidelines for use in the adjuvant setting in patients with EGFR mutation-positive NSCLC following the significant improvement in disease-free survival observed in the Phase III ADAURA trials. Due to limited real-world data in the adjuvant setting, little guidance exists on how to approach potential recurrences either during or after the completion of the treatment. This study aimed to reach a broad consensus on key treatment decision criteria in the events of recurrence. Methods To reach a broad consensus, a modified Delphi panel study was conducted consisting of two rounds of surveys, followed by two consensus meetings and a final offline review of key statements. An international panel of experts in the field of NSCLC (n=12) was used to provide clinical insights regarding patient management at various stages of NSCLC disease including patient monitoring, diagnostics, and treatment approach for specific recurrence scenarios. This study tested recurrences occurring 1) within or outside the central nervous system (CNS), 2) during or after the adjuvant-osimertinib regimen in NSCLC disease which is 3) amenable or not amenable to local consolidative therapy. Results Panellists agreed on various aspects of patient monitoring and diagnostics including the use of standard techniques (e.g., CT, MRI) and tumour biomarker assessment using tissue and liquid biopsies. Consensus was reached on 6 statements describing treatment considerations for the specific NSCLC recurrence scenarios. Panellists agreed on the value of osimertinib as a monotherapy or as part of the overall treatment strategy within the probed recurrence scenarios and acknowledged that more clinical evidence is required before precise recommendations for specific patient populations can be made. Discussion This study provides a qualitative expert opinion framework for clinicians to consider within their treatment decision-making when faced with recurrence during or after adjuvant-osimertinib treatment.